Out and about: Subsequent memory effect captured in a natural outdoor environment with smartphone EEG. (18th January 2019) - Piñeyro Salvidegoitia, Maria; Jacobsen, Nadine; Bauer, Anna‐Katharina R.; Griffiths, Benjamin; Hanslmayr, Simon; Debener, Stefan
Abstract: Spatiotemporal context plays an important role in episodic memory. While temporal context effects have been frequently studied in the laboratory, ecologically valid spatial context manipulations are difficult to implement in stationary conditions. We investigated whether the neural correlates of successful encoding (subsequent memory effect) can be captured in a real‐world environment. An off‐the‐shelf Android smartphone was used for wireless mobile EEG acquisition and stimulus presentation. Participants encoded single words, each of which was presented at a different location on a university campus. Locations were approximately 10–12 m away from each other, half of them with striking features (landmarks) nearby. We predicted landmarks would improve recall performance. After a first free recall task of verbal stimuli indoors, participants performed a subsequent recall outdoors, in which words and locations were recalled. As predicted, significantly more words presented at landmark locations as well as significantly more landmark than nonlandmark locations were recalled. ERP analysis yielded a larger posterior positive deflection during encoding for hits compared to misses in the 400–800 ms interval. Likewise, time‐frequency analysis revealed a significant difference during encoding for hits compared to misses in the form of stronger alpha (200–300 ms) and theta (300–400 ms) power increases. Our results confirm that a vibrant spatial context is beneficial in episodic memory processing and that the underlying neural correlates can be captured with unobtrusive smartphone EEG technology. The advent of mobile EEG technology promises to unveil the relevance of natural physical activity and natural environments on memory. Abstract : This study is the first to use smartphone mobile EEG to capture neural correlates of successful memory formation in the real world. Participants encoded words at outdoor campus locations while on smartphone EEG recording. Crucially, our encoding setting closely resembled the day‐to‐day episodic memory experience, by providing a unique temporal and spatial context for every encoding stimulus, thereby overcoming the invariant spatial context of stationary laboratory settings. Further, we were able to explore the positive impact of feature‐rich locations (landmarks) on episodic memory performance. The advent of mobile EEG technology promises to unveil the relevance of natural environments on memory.